COMPUTER APPLICATIONS TECHNOLOGY TEACHING: A CASE OF SUPPORTING SECONDARY SCHOOL CURRICULUM IMPERATIVES - Bulelwa Makena; Primrose Zameka Yengwayo (International Journal of Innovative Technologies in Social Science, 2023)
The purpose of this study was to determine whether Computer Applications Technology secondary school teachers receive necessary support. Qualitative approach was chosen because it incites the most important meaning from participants and best suited for small samples. As case study embedded this investigation. A case study was used for this qualitative paper with an aim to investigate whether Computer Applications Technology teaching was supported to enhance secondary school curriculum imperatives. Three participants were selected purposively from a rurally located Eastern Cape Education District. To collect data, semi-structured interviews were used. Data were analysed thematically. Findings indicated that teachers do not receive necessary support on technology use, this caused by insufficient school funds to render trainings towards upskilling human resource for expected content knowledge. The paper recommends that school authorities need to support teachers and learners as CAT is one of the vital subjects underpinning school curriculum. In conclusion, school authorities is obliged to render support towards developed computer literacy skills.